Checklist feasibility and impact in gastrointestinal endoscopy: a systematic review and narrative synthesis - Bitar, Véronique; Martel, Myriam; Restellini, Sophie; Barkun, Alan; Kherad, Omar (Endoscopy International Open, 2021)
Background and study aim Checklists prevent errors and have a positive impact on patient morbidity and mortality in surgical settings. Despite increasing use of checklists in gastrointestinal endoscopy units across many countries, a summary of cumulated experience is lacking. The aim of this study was to identify and evaluate the feasibility of successful checklist implementation in gastrointestinal endoscopy units and summarise the evidence of its impact on the commitment in safety culture.Methods A comprehensive literature search was performed identifying the use of a checklist or time-out in endoscopy units from 1978 to January 2020 using OVID MEDLINE, EMBASE, and ISI Web of Knowledge databases, with search terms related to checklist and endoscopy. We summarised overall adherence to checklists from included studies through a narrative synthesis, characterizing barriers and facilitators according to nurse and physician perspectives, while also summarizing safety endpoints.Results The seven studies selected from 673 screened citations were highly heterogeneous in terms of methodology, context, and outcomes. Across five of these, checklist adherence rates post-intervention varied for both nurses (84 % to 96 %) and physicians (66 % to 95 %). Various facilitators (education, continued reassessment) and barriers (lack of safety culture, checklist completion time) were identified. Most studies did not report associations between checklist implementation and clinical outcomes, except for better team communication.Conclusion Implementation of a gastrointestinal endoscopy checklist is feasible, with an understanding of relevant barriers and facilitators. Apart from a significant increase in the perception of team communication, evidence for a measurable impact attributable to gastrointestinal checklist implementation on endoscopic processes and safety outcomes is limited and warrants further study.